Faktor-Faktor yang Mempengaruhi Kualitas Pelaporan Keuangan Publik di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Jawa Tengah - Attar Dian Suprapti (Syntax Idea)
The low quality of financial reports can lead to public distrust in the financial management conducted by local governments. Local governments should ideally represent the community in governing, making accountable and transparent financial management a mandatory practice. The aim of this research is to examine the factors influencing public financial management. This research is quantitative in nature. The research design employed is quantitative. The population of this study comprises staff members of the Investment and Integrated One-Stop Service Agencies (DPMPTSP) of Central Java Province. Due to the limited number of staff in the DPMPTSP of Central Java Province, all staff members will be included as research samples. Data analysis involves screening and transforming the collected information to achieve results. The research results yielded a significant value of p = 0.113, indicating the absence of empirical support for Hypothesis 1. This suggests that the use of IT does not have a significant influence on the quality of government financial reports.